PENGARUH ORIENTASI KEWIRAUSAHAAN, INOVASI PRODUK, DAN DUKUNGAN PARTNER TERHADAP KEUNGGULAN BERSAING (STUDI PADA INDUSTRI MAKANAN DAN MINUMAN SKALA KECIL DAN MENENGAH DI KOTA SEMARANG) - Puspasari, Elisabeth Lisato; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2017)
Industry in Indonesia been growing well from year to year, including growth in the food and beverage industry. More businessman interested and join the food and beverage industry nowadays. Many ways businessman do to win the competition in the industry or also known as competitive advantage. This research’s objectives are to test the influence of entrepreneurial orientation, product innovation, and partnership support against the competitive advantage of food and beverage industry in Semarang city.Taking a sample of 150 respondents from businessman in food and beverage industry in Semarang city using simple random sampling technique selecting respondents. The method of data analysis used is multiple regression analysis, where the analysis consist of validity test, reliability test, classical assumption test, multiple linear regression test, t test, and F test.The result of multiple regression analysis shows that product innovation variable (0.363)and partnership support (0.152) variable have positive and significant influence to competitive advantage, while entrepreneurial orientation (0.087)has positive but not significant influence to competitive advantage.